Study of Mechanical and Physical Properties for SiC/ Al Composites - Amera G. Baker (Institute of Advanced Engineering and Science, 2013)
The micro-structural changes and mechanical properties were investigated in an Al reinforced with SiC particles which synthesized using powder technology technique. SiC/Al composites containing four different weight percentages 40%, 50%, 60% and 70% of SiC. X-ray diffraction was used to characterization and observes the phases formed in the process of sintering at different temperatures (800 0C, 1100 0C). Crystallite sizes calculated from Scherer relation, the grain size of the SiC/Al are observed to increase with the increasing in the sintering temperature of the samples. The hardness tests were conducted in the suitable Hardness Testing Apparatus by choosing appropriate scales of loading and measurement. The test revealed a marked increase in the Vickers hardness with respect to the base composites as well as silicon carbide. It was found from the experimentation that the hardness rate increases with increasing weight fraction of silicon carbide (SiC) and sintering temperature. The best results have been obtained at 70% weight fraction of SiC particles at 1100 0C. The aim of this investigation is to obtain the fundamental understanding of the micro structural changes of the Al matrix composites reinforced with SiC particles and mechanical properties.